Pengaruh layanan pengiriman makanan terhadap meningkatkan penjualan pengusaha Kuliner - Fahreza, Mohammad; Arisena, Adri; Zhafira, Nabila Ayu (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research was backgrounded by culinary SMEs or Jatinangor culinary entrepreneurs whose sales fell due to Covid-19 in 2020. To suppress the spread of Covid-19, the Government recommends one of them by using digital transactions. This study aims to find out how GoFood's food delivery service has an influence on increasing culinary sales in Jatinangor. What efforts should be made by the GoFood food delivery service application in increasing sales of culinary entrepreneurs in Jatinangor. The methods used are hypothesis testing and case studies by describing each related factor through interviews and literature studies. The object of this study is culinary business actors or culinary SMEs registered in the GoFood Jatinangor application. The data obtained are processed by distributing questionnaires, field interviews and based on t-tests and coefficients of determination. The results showed that GoFood food delivery services had an effect on increasing sales of culinary entrepreneurs or Culinary MSMEs in Jatinangor, so that GoFood food delivery services should minimize or not change the rules for profit sharing costs and carry out promotional programs for new members or restaurants